Notas para uma distinção entre civilização e cultura - Soveral, Eduardo Abranches de, 1927-2001 (1986)
The Author makes a phenomenological description and a characterization of human acts that aim at dominion as well as of those which are intended to be expressive and significant.Basing himself on these two kinds of acts he tries to characterize Politics, Economics and Pedagogy, and, by the way, criticizes Max Weber's distinction between, «conviction ethics» and «responsiibility ethics».At last he uses the two analyses to elucidate the concepts of culture and civilization.